Evaluation of Distributed Energy Resource Interconnection Codes and Grid Ancillary Services of Photovoltaic Inverters: A Case Study on Dubai Solar Programme - Shahin, Moustafa; Topriska, Evangelia; Nour, Mutasim; Gormley, Michael (International Journal of Energy Economics and Policy, 2020)
This paper evaluates the technical aspects of grid-connected photovoltaic (PV) systems and distributed energy resources (DERs) interconnection grid codes. The advanced functions of smart PV inverters and smart grid solutions are discussed as well as the gaps of the existing grid codes that hinder DER ancillary services. An online survey targeted the key stakeholders and industry experts have been conducted to investigate advanced inverters potential of providing DER ancillary services to distribution grids. The survey results are discussed in details and recommendations for the reactive power support of DER inverters and DER interconnection codes enhancements are presented. Keywords: Distributed Energy Sources, Distributed Energy Resource Interconnection Grid Codes, Distributed Energy Resource Ancillary Services, Distributed Energy Resource Integration, Advanced Inverters Capabilities, Volt/Var Control JEL Classifications: P48, Q42, Q48 DOI: https://doi.org/10.32479/ijeep.8758